The effect of the Joyce and Will model on the acquisition of grammatical concepts for second-grade intermediate students (Journal of the College of Basic Education, 2023)
The aim of the research is to impact on the active template of Joyce and Will Visab grammatical concepts for second-grade students average research objective The researcher chose an experimental design from the designs of tight control for one control group, a dimensional test and medium-volitional abilities , to conduct the experiment. The research sample consisted of 74 female students and distributed to my group of them. The experimental group consisted of (36) students in grammatical concepts according to Joyce and Will model, while the control group consisted of (38) students in grammatical concepts according to the usual method, and the equivalence process was conducted Between the two groups, the following variables were investigated: age, female students’ grades in Arabic grammar for the first course of the second grade, intermediate, and the parents’ academic achievement. Statistical treatments There are no differences between the two groups in these variables Then the researcher prepared in the acquisition of grammatical concepts consisting of (24) paragraphs and for the purpose, the validity offered by the researcher on the apparent honesty of the researcher on the apparent honesty on a general exploratory sample to measure the level of ease, difficulty and strength of analysis in relation to the acquisition of grammatical concepts, and then applied the analysis in relation to the acquisition of grammatical concepts The results, after being statistically processed, showed that there was a significant difference in the significance of the two research groups at the level (0.05) and for the knowledge of the direction of the direction and which groups had excelled, the researcher used the usual method. In light of the results reached by the researcher, the archaeological areas that found interest recommended that the Joyce and Will model, as it works to establish the correct response and evaluate the wrong answer. Similar studies to study in the stages and classes of Geneina.